2019
DOI: 10.1002/gps.5062
|View full text |Cite
|
Sign up to set email alerts
|

The impact of apathy on cognitive performance in the elderly

Abstract: Objectives To examine the impact of apathy on cognitive performance in the elderly following the conceptual principles proposed by Marin 1 and Stuss et al 2 and to determine the role of the symptoms of apathy in different cognitive domains. Methods Cross‐sectional study with a cohort of healthy elderly subjects over 55 years old (n = 140). One hundred forty healthy‐elderly subjects (aged 79.24 ± 8.6 years old) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
3
20
2
2
Order By: Relevance
“…Psychiatric measures were included as they can affect cognitive abilities, likely due to a variety of factors including anhedonia, decreased motivation, concentration difficulties and impairments in attention and processing speed. 19 In addition to using propensity score matching, we verified our results using covariate adjustment, based on the findings by Elze et al, 20 which showed that this more conventional technique may be the most reliable method for the analysis of observational databases. To do this, we compared the yearly rate of change between the group taking antidopaminergic medication (n=2369) and the group of non-takers (n=2642) using a univariate analysis of variance (ANOVA) with the following covariate variables: age, gender, CAG repeat length, DBS, TFC and time since diagnosis (see online supplementary section).…”
Section: Discussionsupporting
confidence: 74%
“…Psychiatric measures were included as they can affect cognitive abilities, likely due to a variety of factors including anhedonia, decreased motivation, concentration difficulties and impairments in attention and processing speed. 19 In addition to using propensity score matching, we verified our results using covariate adjustment, based on the findings by Elze et al, 20 which showed that this more conventional technique may be the most reliable method for the analysis of observational databases. To do this, we compared the yearly rate of change between the group taking antidopaminergic medication (n=2369) and the group of non-takers (n=2642) using a univariate analysis of variance (ANOVA) with the following covariate variables: age, gender, CAG repeat length, DBS, TFC and time since diagnosis (see online supplementary section).…”
Section: Discussionsupporting
confidence: 74%
“…3,12,13 Apathy is a complex syndrome characterized by a persistent lack of motivation not attributable to altered levels of consciousness that may affect selfgenerated behaviours, cognitive performance, and emotional-affective processing. 14,15 It has been shown to be the most common syndrome in degenerative dementia and is strongly associated with higher cognitive impairments. [15][16][17][18] Apathy is related to executive impairment and the capacity of the frontal cortex to select, initiate, maintain, and shift actions.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has been shown to be the most common syndrome in degenerative dementia and is strongly associated with higher cognitive impairments. [15][16][17][18] Apathy is related to executive impairment and the capacity of the frontal cortex to select, initiate, maintain, and shift actions. 19,20 Less attention is paid to apathy than other BPSD, possibly because in an institutional context it is less intrusive, despite being directly linked with high levels of disability in PWD.…”
Section: Introductionmentioning
confidence: 99%
“…cognitive apathy dimension) 16,17 . In fact, a higher level of apathetic symptoms rated on behavioural scales is robustly associated with poorer executive functioning in non‐demented older adults, especially in spontaneous flexibility, inhibition, and working memory, 9,10,18 which is in line with the hypothesis that executive impairment is one of several psychological components involved in manifestations of apathy 6 . Executive impairment appears to be both a consequence and a crucial factor in the onset of apathy, but little is known about its specific association with apathy subdomains.…”
Section: Introductionmentioning
confidence: 67%